2018
DOI: 10.1007/978-3-030-00934-2_8
|View full text |Cite|
|
Sign up to set email alerts
|

Towards a Glaucoma Risk Index Based on Simulated Hemodynamics from Fundus Images

Abstract: Glaucoma is the leading cause of irreversible but preventable blindness in the world. Its major treatable risk factor is the intra-ocular pressure, although other biomarkers are being explored to improve the understanding of the pathophysiology of the disease. It has been recently observed that glaucoma induces changes in the ocular hemodynamics. However, its effects on the functional behavior of the retinal arterioles have not been studied yet. In this paper we propose a first approach for characterizing thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Regarding clinical relevance, a recent study on diabetic retinopathy showed that a combination of fundus and OCTA measurements can already improve assessment of the disease (130). Another study used a fundus-based model to generate a fixed length feature vector as an index that can be used to successfully discriminate between healthy and glaucoma (96). However, since they used constant, nonindividualized inlet values and relied on the vessel structure to guide the outcome, the end point parameters are not easily interpretable.…”
Section: Physiological Implications and Clinical Relevancementioning
confidence: 99%
“…Regarding clinical relevance, a recent study on diabetic retinopathy showed that a combination of fundus and OCTA measurements can already improve assessment of the disease (130). Another study used a fundus-based model to generate a fixed length feature vector as an index that can be used to successfully discriminate between healthy and glaucoma (96). However, since they used constant, nonindividualized inlet values and relied on the vessel structure to guide the outcome, the end point parameters are not easily interpretable.…”
Section: Physiological Implications and Clinical Relevancementioning
confidence: 99%
“…It also includes the disc and cup segmentation. DR HAGIS (Holm et al, 2017), HRF (Odstrcilik et al, 2013), and LES-AV (Orlando et al, 2018) are small sets with 39, 45 and 22 images, respectively, with no disc and cup segmentation. The ACRIMA set (Diaz-Pinto et al, 2019) contains 396 images from patients with glaucoma and 309 images from healthy patients.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, the lists of datasets used for segmenting and classifying retina fundus images are discussed. This datasets are listed in order of usage, they include: DRIVE [125], STARE [126], CHASE-DB1 [127], HRF [128], MESSIDOR [129], IOSTAR [130], ORIGA [131], REFUGE [131], DB1 [132], DB0 [133], Kaggle dataset, DRISHTI-GS [134], NIVE [135], RIM-ONEr3 [136], DRIONS-DB [137], RITE [138], WIDE [139], SYNTHE [140], LES-AV [141], RIGA [142], DUKE, DCA, EIARG1, and AV-INSPIRE. The list of datasets that have the highest usage is shown in Fig.…”
Section: Datasetsmentioning
confidence: 99%